Surgical Outcomes from Lichtenstein Inguinal Hernioplasty using Polypropylene Suture Vs Skin Staples for Mesh Fixation - Humaal Ahsan, Marya Saleem, Mohammad Akmal Shafiq, Muhammad Asadullah Khawaja, Usama Shabbir (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare surgical outcome of polypropylene suture and skin staples for securing mesh in Lichtenstein Inguinal Hernioplasty Methodology: There were a total of two hundred people with an inguinal hernia who were involved in the study. They were randomly randomized to receive either polypropylene mesh or staples. Each patient voluntarily undergoes a Lichtenstein tension-free inguinal hernioplasty at the THQ Kherpur operating room. This procedure is performed under spinal anesthesia, and rigorous hygiene standards are adhered to throughout the procedure. In Group A, the anchorage of the mesh was conducted using 2/0 polypropylene suture, whereas in Group B, the anchorage of the mesh was accomplished using skin staples. Both methods were successful in achieving the desired results. The operating time, total surgical time, and wound infection rates were all compared between the groups. Results: The common age in cases of Group-X 36.52+9.41 years, and 38.63+8.76 years in Group B cases. Mean postoperative pain was 2.16+1.98 in Group-X and 1.46+1.24 in Group-Y, both of which had p values of 0.0001. Mean postoperative duration in Group-X was 56.7+5.47 and 48.54+4.38 in Group-Y, both of which had p values of 0.0001. The percentage of patients who had a post-operative wound infection was reported as 22 (22%) in Group-X and 6 (6% in Group-Y), whereas 78 (78%) in Group-X and 94 (94%) in Group-Y did not develop an infection; the p value for this comparison was 0.0011. Conclusion: When performing a Lichtenstein inguinal hernioplasty, anchoring the mesh with skin staples rather than polypropylene suture results in a reduction in both the average amount of time needed for the operation as well as the amount of postoperative pain experienced by the patient. Keywords: Inguinal Hernioplasty, skin staples, polypropylene suture, outcome